2020
DOI: 10.1186/s42358-020-0121-5
|View full text |Cite
|
Sign up to set email alerts
|

Real - rheumatoid arthritis in real life - study cohort: a sociodemographic profile of rheumatoid arthritis in Brazil

Abstract: Background: In Brazil, socioeconomic differences in the incidence of rheumatoid arthritis (RA) have been demonstrated, which are important in the formulation of hypotheses regarding the association between environmental factors, lifestyle and the risk of disease development. This study examines how the socioeconomic condition of the patient with RA in Brazil, assessed according to social class, educational level, employment situation and use of caregivers, affects the times between the beginning of symptoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Most studies were cross-sectional. In six studies, the autoimmune rheumatic disease assessed was rheumatoid arthritis [9][10][11][12][13][14] . The remaining two studies evaluated systemic lupus erythematosus 15,16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were cross-sectional. In six studies, the autoimmune rheumatic disease assessed was rheumatoid arthritis [9][10][11][12][13][14] . The remaining two studies evaluated systemic lupus erythematosus 15,16 .…”
Section: Resultsmentioning
confidence: 99%
“…Sacilotto et al 9 Employment status Individual questionnaire; medical records used as secondary sources…”
Section: How Work Outcomes Were Assessed Work-related Findingsmentioning
confidence: 99%
“…This finding corroborates with Gong et al (2019) [ 31 ] where the authors found a modest negative linear correlation between Sharp and HAQ scores and longer disease duration (p< 0.001) in Chinese RA patients. In addition, in the REAL—Rheumatoid Arthritis in Real Life in Brazil [ 32 ], the authors demonstrated that the patients with erosion showed an HAQ-DI value higher than those without erosion. Therefore, from our findings, low muscle strength, worse physical performance and the presence of bone erosion seem to influence the HAQ score in patients with RA.…”
Section: Discussionmentioning
confidence: 99%
“… 45 In Brazil, there are socioeconomic disparities in the incidence of RA, which are related to environmental factors, lifestyle and disease development risks. 46 A meta-analysis revealed that the overall prevalence of RA in South Africa is 2.5%. 47 The prevalence of RA in South Africa is significantly higher than that in other BRICS countries.…”
Section: Discussionmentioning
confidence: 99%